2007
DOI: 10.1002/j.1556-6678.2007.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Violence Risk: A Review and Clinical Recommendations

Abstract: Guidance to identify and manage clients with a perceived high risk for future violence is of great importance for mental health professionals. In the past decade, several structured instruments have been developed to assess risk of future violence. Awareness of the limits and abilities of such instruments is required. This article reviews the most well-known risk assessment tools and provides recommendations for how to approach the area of violence risk assessment.Earn 1 CE credit now for reading this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Minority ethnic groups seem to have a higher chance of being involved in violence 18 . In addition, younger individuals with learning disabilities and history of bipolar parents, and adolescents with conduct disorders have a higher incidence of violence [18][19][20] .…”
Section: Workplace Violence In Healthcare -An Emerging Occupational Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Minority ethnic groups seem to have a higher chance of being involved in violence 18 . In addition, younger individuals with learning disabilities and history of bipolar parents, and adolescents with conduct disorders have a higher incidence of violence [18][19][20] .…”
Section: Workplace Violence In Healthcare -An Emerging Occupational Hmentioning
confidence: 99%
“…Violence is common among patients in substance abuse wards, psychiatric wards, ICUs and emergency departments [18][19][20] .…”
Section: Workplace Violence In Healthcare -An Emerging Occupational Hmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough assessment also includes assessing for risk factors that may place the client at risk for homicide. Haggard-Grann (2007) reported that risk assessment should go beyond the basic prediction of whether partner violence will occur, suggesting instead that counselors attempt to elicit more specific information related to the prediction of IPV such as "what, when, where, and to whom" the violence might occur (p. 299).…”
Section: Predictors Of Escalated Violence or Homicidementioning
confidence: 99%
“…Results yielded from many standardized assessments for either format provide counselors with cut scores that classify clients within a categorical group related to diagnosis or level of risk. Although there is a long-standing history of research investigating the accuracy of clinician-administered versus self-report assessments for making actuarial decisions related to learning disabilities (Benson & Newsome, 2010), self-injury (Bouch & Marshall, 2005), violent behavior toward others (Haggård-Grann, 2007), and degree of rehabilitation (Bengtson & Långström, 2007), there are fewer published studies evaluating these formats related to PTSD (Bury & Bagby, 2002; Calhoun, Boggs, Crawford, & Beckham, 2009). Furthermore, research comparing the degree that aggregated treatment effect size estimates yielded from these different formats influence the results of meta-analyses and the propagation of evidence-supported practices (ESPs) is limited.…”
mentioning
confidence: 99%